The arginine decarboxylase gene ADC1, associated to the putrescine pathway, plays an important role in potato cold‐acclimated freezing tolerance as revealed by transcriptome and metabolome analyses. (27th November 2018) - Kou, Shuang; Chen, Lin; Tu, Wei; Scossa, Federico; Wang, Yamei; Liu, Jun; Fernie, Alisdair R.; Song, Botao; Xie, Conghua
Summary: Low temperature severely influences potato production as the cultivated potato ( Solanum tuberosum ) is frost sensitive, however the mechanism underlying the freezing tolerance of the potato is largely unknown. In the present research, we studied the transcriptome and metabolome of the freezing‐tolerant wild species Solanum acaule ( Aca ) and freezing‐sensitive cultivated S. tuberosum ( Tub ) to identify the main pathways and important factors related to freezing tolerance. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway annotation indicated that polyamine and amino acid metabolic pathways were specifically upregulated in Aca under cold treatment. The transcriptome changes detected in Aca were accompanied by the specific accumulation of putrescine, saccharides, amino acids and other metabolites. The combination of transcriptome and metabolome analyses revealed that putrescine exhibited an accumulative pattern in accordance with the expression of the arginine decarboxylase gene ADC1 . The primary role of putrescine was further confirmed by analyzing all three polyamines (putrescine, spermidine, and spermine) and the genes encoding the corresponding enzymes in two sets of potato genotypes with distinct freezing tolerance, implying that only putrescine and ADC1 were uniquely enhanced by cold in the freezing‐tolerant genotypes. The function of putrescine was further analyzed by its exogenous application and the overexpression of SaADC1 in S. tuberosum cv. E3, indicating its important role(s) in cold‐acclimated freezing tolerance, which was accompanied with the activation of C‐repeat binding factor genes (CBFs). The present research has identified that the ADC1 ‐associated putrescine pathway plays an important role in cold‐acclimated freezing tolerance of potato, probably by enhancing the expression of CBF genes. Significance Statement: Low temperature severely influences potato production as the cultivated potato ( Solanum tuberosum ) is frost sensitive, however the mechanism underlying freezing tolerance of potato is largely unknown. The cold‐responsive genes and metabolites of freezing‐tolerant wild species Solanum acaule were identified and the arginine decarboxylase gene ADC1 ‐associated putrescine pathway was demonstrated to contribute functionally to potato cold‐acclimated freezing tolerance probably through the upregulation of C‐repeat binding factor gene expression.